64.7k views
2 votes
It has two what y equals so idk which one to solve or plug in(...I'm running out of points...)

y=-3x+6
y=5x+38

User Osgx
by
5.8k points

2 Answers

6 votes
you will equalize the two equations of y so
-3x+6=5x+38
5x+3x=38-6
8x=32
x=4
then you will substitute in the equation of y

User Nairolf
by
6.0k points
3 votes
Just plug in one of the other (doesn't matter which one) so it will look like
-3x+6=5x+38
or
5x+38=-3x+6 (it's the same thing as the first one)
Then you solve for x and you substitute that value so you can get y.
Hope this helped :)
User Hirak
by
5.3k points